Agile in practice, a systemic approach - Ruiz de Mendarozqueta, Álvaro (2020)
The relationship between software engineering practices and agile fundamentals are explored. The con-tents of the Agile Manifesto state several principles such as a focus on working software, customer satisfaction, and simplicity among others. This paper explores how agile creates value at a fundamental level by introducing the capability for the organization to take continuously decisions, which are modelled as options. And how this addi-tional value can be eroded by having deviation on classical software engineering parameters, such as Cost of Poor Quality or Phase Containment of errors. Additional focus on traditional software engineering best practices are proposed as the best way to achieve the benefits of the Agile paradigm is by combining it with mature engineering practices. Those practices are well known in the industry and academia. There are different sources that can be searched like SWEBOK and CMMI. As CMMI is organized in maturity levels the model can guide the engineering practices adoption.